Investigation of Lancifortarene (LNF)-Zinc Oxide Nanocomposites for Antidiabetic Applications - Farooq, Tahir; Hameed, Arruje; Fakhar-e-Alam, M.; Saadullah, Malik; M.Adnan; Imran, Muhammad; Asher, Ambreen; Sikandar, Shahzad; Khalid, Tanzeela; Arshad, Sarmad Frogh; Arshad, Hasan Junaid; Anwar, Muhammad; et al. (BioNanoScience, 2025)
Over the last few decades, diabetes mellitus has emerged as the biggest health issue around the globe. The currently available therapeutic options including insulin therapy pose some serious complications. Therefore, there is a great demand for the development of smart, fast-acting, and phyto-based antidiabetic agents with minimal risks. Considering the antioxidant and antidiabetic potential of chitosan (CS) and the newly reported compound lancifortarene (LNF) and the regulatory role of zinc for insulin production, this study aimed to prepare a nanocomposite as LNF-ZnO/CS-NC showing a possible synergistic antidiabetic potential in streptozotocin-induced diabetic rats. The animals were grouped as the negative control, positive control (diabetic rats without treatment), diabetic rats treated with nanocomposite as 50 mg/Kg body weight and 200 mg/Kg of body weight. The NC treatments activated antioxidant machinery, protected structural integrity of the pancreatic β-cells thus regulated insulin production and controlled blood glycemic levels in STZ-diabetic subjects. The NC treatments positively influenced liver function by significantly reducing ALT and AST activities and improved the serum lipid profile. Histopathological studies showed the NC-mediated improvement of hepatic architecture and regeneration of damaged pancreatic β–cells. The 200 mg NC treatment induced antidiabetic effects comparable to the standard drug. Thus, the prepared NC could be a potential candidate for antidiabetic therapy.